An evaluation of the material English for chefs" for the first year students in the cooking class at Hai Phong Technological and Vocational Training School = Đánh giá giáo trình "Tiếng Anh chuyên ngành chế biến món ăn" cho học sinh năm thứ nhất ngành Chế - Nguyễn, Thị Ngọc Châu (ĐHNN, 2017)
Chapter 1: Literature review. Chapter 2: Research methodology. Chapter 3: Data analysis. Chapter 4: Discussion and adaptation